Salesforce Lightning recipes - Shah, Syed Chand; Safari eBooks ([Place of publication not identified] : Packt, 2018)
"The new Lightning Experience combines three major components--Lightning Design System, Lightning App Builder, and Lightning Components--to enable anyone to quickly and easily create beautiful, modern enterprise apps. If you wish to take up the challenges that Lightning throws at you head-on, then look no further because this practical video course will be your faithful companion and ensure that you make best use of the Lightning platform. This video course starts by walking you through the three major Lightning components and will help you enable and configure a Lightning solution. You will explore the art of working with standard components and build a basic layout for the application. Then, you will add more advanced components using the Lightning framework. Finally, you will also build and migrate reports and dashboards to make your app look more professional. Towards the end of the course, you'll make use of the Design System to work with Salesforce data and lay out the entire page with the components that you've built, before integrating Visualforce in your application."--Resource description page.
Presenter, Syed Chand Shah.
Title from title screen (viewed March 22, 2018).
Date of publication from resource description page.
Keywords: Salesforce (Online service); Customer relations -- Management -- Data processing; Sales management -- Data processing; Dashboards (Management information systems); Electronic books